Eforts to improve volleyball underhand passing learning through poison ball games in class XI-3 at SMAN 7 Kediri City - Vicky Nusa Prasety Zulkarnain; Budiman Agung Pratama; Miftahkodin Miftahkodin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to improve the learning of volleyball underhand passing through the poison ball game method in class XI-3 students of XI-3 SMAN 7 Kediri in 2025. This research is a Classroom Action Research (PTK) which consists of two cycles, each cycle consisting of 2 meetings. The subjects of this study were 32 students in class XI-3 SMAN 7 Kota Kediri. The instrument used for data collection in this study was the bottom passing assessment sheet, Based on the results of observations, discussion and research results, it can be concluded that learning to pass down through the poison ball game method in class XI-3 SMAN 7 Kota Kediri for 2 cycles can improve student achievement. This can be proven from the results of observing the student learning outcomes of 32 students. In the initial conditions, the number of students who achieved a KKM score of 80 was only 6 to 7, and in the first cycle it increased to 15 students, then in cycle II, it increased to 29 students who achieved the KKM score. 80 or more. So that the classical completeness in the class is more than 75% of students who have finished studying.